KEGIATAN EKSTRAKURIKULER KEAGAMAAN DALAM PEMBENTUKAN MORALITAS SISWA DI SMPN 1 DIWEK DAN SMPN 2 JOMBANG - Beny Sinta Sari (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2020)
Extracurricular activities are educational activities outside the subject and counseling services to help the development of students according to their needs, potential, talents, and interests. Through extracurricular activities, it is expected to help in the process of moral formation of students, as well as its application in SMP N 1 Diwek and SMPN 2 Jombang. This research uses a descriptive qualitative approach. Results of the study: (1) The morality of students in SMP N 1 Diwek and SMP N 2 Jombang, namely spiritual, honest, responsibility, discipline, mutual cooperation, tolerance, self-confidence, and courtesy. (2) The implementation of extracurricular activities in the form of reading the Qur'an, praying in congregation, recitation and sadaqah routinely every day and adjusted to the activity schedule itself with structured; (3) Similarities and differences in extracurricular activities at SMP N 1 Diwek and SMP N 2 Jombang are that each school has a program that is in accordance with the government's stipulation, except for additional programs according to school needs. The difference from the location or environment around each school is in the city center and the community environment.